New insights on post-fire morels (Morchella spp.) in Italy - Snabl, Martin; Guidori, Urbano; Gianchino, Carmelo; Leonardi, Marco; Zambonelli, Alessandra; Iotti, Mirco (Phytotaxa, 2023)
Morels (Morchella spp.) fruit abundantly in burnt sites, in particular the year following the fire event. In the post-fire context, ascomata with densely tomentose surfaces, herein called “hair-bearing morels”, have also been reported in the literature. In this work, two morphotypes of hair-bearing morels from burnt pine forests of northern and central Italy are described and their ITS rDNA regions sequenced. The first was identified as M. tomentosa, which represents the first evidence of this species outside North America. For the second hair-bearing morphotype, the new forma M. vulgaris f. atrovelutipes is proposed. Our results suggest that the “tomentose” trait in morels is not only species-specific to M. tomentosa but it can also occasionally occur in other morel species after a fire event. In addition, taxonomic history of hair-bearing morels is reviewed and discussed.